Perception of online learning with anxiety and stress level among medical students - Dewanti, Nanda Derista Ayu; Nugroho, I Gusti Bagus Indro; Lestari, Anik; Yuliadi, Istar; Ilyas, Muhana Fawwazy; Triniputri, Winastari Yarhanim (Majalah Kedokteran Andalas, 2023)
Objective: This study aimed to find out the association between the perception of online learning and anxiety as well as stress levels among medical students. Methods: This is an observational analytic study with a cross-sectional approach. The sample was comprised of 213 undergraduate medical studentsept at Medical Faculty Universitas Sebelas Maret (UNS) and data were collected using total sampling. The study was conducted using the Taylor Manifest Anxiety Scale (TMAS), Perceived Stress Scale (PSS), and perception of online learning questionnaires. Data were analyzed using Chi-square, Cramer’s V, and Kendall tau b test. Results: This study shows a significant correlation between the perception of online learning and anxiety (p=0.049) as well as stress level (p=0.007). Sex also has an association with anxiety (p=0.010) and stress level (p=0.004). Furthermore, female has higher anxiety and stress levels compared to male. Conclusions: Perception of online learning is related to the anxiety and stress level among medical students.